APRI Profile of Cirrhotic Patients with Positive HBsAg - Nadya Husni; Leonita Anniwati; Lina Lukitasari (Faculty of Medicine Universitas Airlangga, 2019)
Introduction: Hepatitis B is a viral infection that has the potency to become chronic infection and cause serious complications such as liver cirrhosis and hepatocellular carcinoma. One of the tools in diagnosing hepatitis B or cirrhosis and predicting the prognosis is aspartate aminotransferase to platelet ratio index (APRI). The purpose of this study is to evaluate the profile of APRI among cirrhotic patients with positive hepatitis B surface antigen (HBsAg).Method: This research was a descriptive observational study. The number of samples was 35 cirrhotic patients with positive HBsAg in RSUD Dr. Soetomo Surabaya from January-December 2017.Results: The majority of cirrhotic patients had >1,5 APRI score (48,57%). The most prevalent APRI score in Child A patients for first classification was 0,5 – 1,5 (5,71%) while for second classification was 0,7 – 1,5 (5,71%). The most prevalent APRI score in Child B patients for first classification was 0,5 – 1,5 (17,14%) while for second classification was 0,7 – 1,5 (11,43%). Most of Child C patients had >1,5 APRI score (22,86%). The majority of malignant degeneration patients also had >1,5 APRI score (14,29%).Conclusion: The majority of cirrhotic patients had >1,5 APRI score. In cirrhotic patients with Child A or B classification, the increase of APRI score was not as much as those with Child C or malignant degeneration classification.Keywords: Hepatitis B, cirrhosis, liver, hepatocellular carcinoma, APRI